Characterization of Atmospheric Electrical Discharge in Pin-water Configuration at Different NaCl Concentrations - Nabhan Abdulkareem Hamdon; Murad Mohamed Kadim; Qusay Adnan Abbas (Tikrit Journal of Pure Science)
The interaction between a pin-plate and plasma are representing an interest subject in plasma technology and applications. In this research, the influence of added NaCl to distilled water on the discharge characteristics that formed in the gap between pin-water surfaces was investigated in more details. Their electrical and optical characteristics serve as identifiers. It's found that all optical emissions intensity peaks as a results that detected are decreased with increasing of NaCl concentrations (300,400, and 500 mg). As well as, the emission intensity of neutral emission peaks are much higher than that of the ionic emission peaks. The addition of NaCl changes the liquid accessibility, which alters the kinetics of the discharge that forms in the pin-water surface gap. Also, its observed that the NaCl concentrations affected on the I-V characteristics. The data detected that the plasma frequency ((377.1176 - 279.1951)*1011 rad/sec), electron number density ((4.4519 – 2.4401)*1017 cm-3) and electron temperature (2.1537 – 1.663 eV) decreased with increases of NaCl concentrations except the Debye length ((1.6342 – 1.93989)*10-6 cm) shown a different behavior with increase of NaCl concentrations.